Demonstration of Knowledge by the Neural Network to Provide a Framework for Achieving the Desired Profit in the Financial Planning of the Organization (Case Study: Saipa Company) - Zahra Sadeghi; Mohammad reza Motadel; Abbas Toloie (بازیابی دانش و نظام‌های معنایی, 2022)
Making more profit in organizations requires accurate tools to strengthen the business for proper financial planning. Therefore, the purpose of this study was to demonstrate knowledge of the neural network to provide a framework for achieving the desired profit in the organization's financial planning. This research was of the applied type and was performed by the analytical survey method. The study population was the organizations present in the Exchange and Securities Organization, and the data extracted from the official system of the Exchange and Securities Organization of Iran (Cadal) were used. This research was conducted using the neural network method in a MATLAB program environment. Findings The range of changes of factors affecting the main index in the organization's financial planning (profit) and the most important factors affecting it were determined. The proposed framework was reviewed in three different sets of three various industries and had acceptable results. Therefore, the study results indicated that the proposed framework in this study could be used for other organizations present in the stock exchange and securities.